Evaluasi Konteks Dalam Program Pemberdayaan Masyarakat Pt. Ceria Nugraha Indotama Di Kecamatan Wolo Kabupaten Kolaka - Iswadi Amiruddin; Hasniati Hasniati; Muhammad Yunus (Kolaborasi : Jurnal Administrasi Publik, 2020)
The research objective was to determine the context evaluation in the community empowerment program of PT. Ceria Nugraha Indotama In Wolo District, Kolaka Regency. The method used in this research is a qualitative method. The research was conducted at the PT. Cheers Nugraha Indotama. The research informants were the CSR / PPM Manager, CSR / PPM Consultants, the person in charge of each CSR / PPM field of PT. Cheers Nugraha Indotama. The results showed that the evaluation of the context in the community empowerment program of PT. Ceria Nugraha Indotama In Wolo District, Kolaka Regency on the aspect of the organization of the PT. Ceria Nugraha Indotama has committed both to the provincial government, district government, sub-district government and village heads to carry out the company's obligations, namely the CSR / PPM program to the community, but in the aspect of social mapping / social mapping, the company has identified the needs of the community but it has not been maximized because it seems lack of programs that touch and empower people to improve their lives so that more attention and programs are needed. The suggestion in this research is the need for in-depth social mapping from the team in charge of the company so that the community is able to feel the benefits of its presence.Keywords: Evaluation, context, community empowerment program